Robotic Rectal Cancer Surgery with the da Vinci Xi System: First 100 Cases - Ozben, Volkan; Dogruoz, Alper; Boga, Salih Anil; Aytac, Erman; Baca, Bilgi; Hamzaoglu, Ismail; Karahasanoglu, Tayfun (ISTANBUL TRAINING \& RESEARCH HOSPITAL, 2019)
Introduction: The da Vinci Xi system, the latest model of the robotic technology, is proposed to enable multiquadrant abdominal surgery to be performed in a fully robotic approach without the need for a laparoscopic assistance, robot re-docking or re-positioning of the trocars. However, the literature has limited data on this topic. In this study, we aimed to evaluate the feasibility of the Xi robot use in rectal cancer surgery, a multiquadrant surgical procedure. Methods: Patients undergoing robotic mezorectal excision for rectal adenocarcinoma using the da Vinci Xi system between December 2014 and June 2017 were included in this study. Data were collected prospectively and analyzed retrospectively. Demographic data, perioperative clinical findings, histopathologic data and postoperative 30-day outcomes were analyzed. Results: One hundred patients were included in this study. There were 57 male and 43 female patients with a mean age of 61.4 +/- 12.3 years. Low anterior resection and abdominoperineal recetion were performed in 90 and 10 patients, respectively. In all the operations, the abdominal and pelvic stages of the procedure were completed robotically without a need for dual docking or trocar re-positioning. The mean operative time was 328.4 +/- 105.8 min and blood loss was 131.7 +/- 170.3 mL. Intraoperative complication occurred in 2 patients (2\%). Two procedures were converted to open surgery (2\%). The mean number of harvested lymph nodes was 25.3 +/- 12.0. All the surgical margins were clear except for four patients (4\%). The rate of incomplete mesorectal fascia was 3.2\%. The mean length of hospital stay was 6.6 +/- 3.6 days and the overall postoperative morbidity rate was 25\%. Conclusion: The da Vinci Xi model enables rectal cancer operations to be performed in a fully robotic fashion. This feature of the robot helps surgeon to benefit optimally from the advantages robotic surgery in all stages of the procedure.
Keywords: da Vinci Xi system; rectal cancer; robotik mesorectal excision